Assessment of the mineral ilmenite for U–Pb dating by LA-ICP-MS. Issue 6 (10th May 2021) - Thompson, Jay M.; Goemann, Karsten; Belousov, Ivan; Jenkins, Kate; Kobussen, Alan; Powell, Will; Danyushevsky, Leonid
Abstract : The mineral ilmenite is analysed by LA-ICP-MS for elemental and U–Pb isotopic compositions. A methodology is presented for accurate results using the mineral rutile for U–Pb ages and basaltic reference materials for major and trace elements. Abstract : The chemical composition of the mineral ilmenite is useful in mineral exploration for diamonds and in understanding igneous geological processes. This study develops an analytical methodology for accurate analyses of ilmenite by LA-ICP-MS for major, minor, trace element and U–Pb isotopic compositions. Accuracy of chemical compositions by LA-ICP-MS is monitored by comparing with EMPA and accuracy of the LA-ICP-MS U–Pb ages is verified by comparison to published ages for other mineral geochrometers from the same sample. Variation of laser fluence (2, 3 and 5 J cm −2 ) and calibration materials (Mud Tank zircon, BCR-2g, and TB-1 rutile) are optimized to provide the best accuracy of ilmenite chemical and isotopic compositions. Rutile, as the primary calibration material for Pb/U ratios, produces accurate U–Pb ages within analytical uncertainties. Use of normalization to a 100% metal oxide total for LA-ICP-MS analyses, coupled with mineral stoichiometry calculations, allows for the estimation of Fe 2+ /Fe 3+ ratios that compare well with similar estimates from EMPA (0.23 vs. 0.22 respectively). U–Pb age results from an igneous ilmenite from the Bushveld Complex using this methodology are within uncertainty of the zircon ID-TIMS age of the intrusion (2044 ± 31 Ma (2 s) vs. 2054.4 ± 1.3 Ma (2 s)).